PENGARUH SISTEM AKUNTANSI DAN KOMPETENSI AKUNTANSI TERHADAP PENYALAHGUNAAN DANA DESA DI KECAMATAN BLUTO KABUPATEN SUMENEP - Zelvi Ainun Naja; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2020)
This research was conducted to determine the influence of accounting systems and accounting competencies on misuse of village funds. This research uses a quantitative approach, where this research is a field research (field research) using descriptive quantitative methods. Sources of data in this study are primary data and data collection methods by distributing questionnaires. In this study, there are two independent variables used, namely the Accounting System (X1) and Accounting Competence (X2), while the dependent variable is Misuse of Village Funds (Y). In this study, researchers used a sample with nonprobability sampling method with purposive sampling type obtained a sample of 69 respondents. The results in this study indicate that the accounting system has a positive effect.Keywords: accounting system, accounting competence and misuse of village funds